(untitled) (Italian Review of Legal History, 2024)
Most trials for sexual violence rely on the statements of the victim. Their evaluation is therefore essential for determining the commission of the crime. However, such evaluation can be influenced by gender stereotypes that tend to blame victims of sexual rape, often leading them to waive legal protection, with serious effects on citizens’ trust in the administration of justice. The study on the jurisprudence of the court of Como on carnal violence (article 519 Penal Code 1930) and violent acts of lust (article 521 Penal Code 1930) in the 1970s not only demonstrates that traditional sexist prejudices have often affected the judges’ evaluation, preventing them from determining the guilt of the defendants, but also that their use has been favored by the intrinsic difficulty in establishing the existence of such offenses. Under the Code of Criminal Procedure of 1930, judges extensively resorted to acquittal for lack of evidence, despite the recommendations of the Court of Cassation to interpret the rule restrictively. While, on the one hand, the use of the doubting formula reflected the difficulty in establishing the facts in rape trials, on the other hand, it attributed some relevance to the statements of the offended party. In any case, this solution resulted in a lack of protection both for the victim, who did not obtain justice in the trial, and for the defendant, who continued to suffer negative (both legal and social) consequences even after the closure of the trial.